La Table des rois Contribution à l'histoire textuelle des ›Tables faciles‹ de Ptolémée - Defaux, Olivier (CHRONOI, 2023)
The Table of Kings by Ptolemy, a second-century Alexandrian astronomer, presents a continuous list of rulers from the Neo-Assyrian Empire to the Roman Empire. It is a crucial source for our chronological approach to the ancient Near East and the Mediterranean world. This study presents a description of the Greek manuscript witnesses to the Table of Kings, a new critical edition, and a history of the text up to the modern period.